Dietary supplementation with long-chain monounsaturated fatty acid isomers decreases atherosclerosis and alters lipoprotein proteomes in LDLr−/− mice. (July 2017) - Yang, Zhi-Hong; Gordon, Scott M.; Sviridov, Denis; Wang, Shuibang; Danner, Robert L.; Pryor, Milton; Vaisman, Boris; Shichijo, Yuka; Doisaki, Nobushige; Remaley, Alan T.
Abstract: Background and aims: Concentrated fish oils, containing a mixture of long-chain monounsaturated fatty acids (LCMUFA) with aliphatic chains longer than 18 C atoms (i.e., C20:1 and C22:1), have been shown to attenuate atherosclerosis development in mouse models. It is not clear, however, how individual LCMUFA isomers may act on atherosclerosis. Methods: In the present study, we used saury fish oil-derived concentrates enriched in either C20:1 or C22:1 isomer fractions to investigate their individual effect on atherosclerosis and lipoprotein metabolism. LDLR-deficient ( LDLr −/− ) mice were fed a Western diet supplemented with 5% (w/w) of either C20:1 or C22:1 concentrate for 12 wk. Results: Compared to the control Western diet with no supplement, both LCMUFA isomers increased hepatic levels of LCMUFA by 2∼3-fold ( p  < 0.05), and decreased atherosclerotic lesion areas by more than 40% ( p  < 0.05), although there were no major differences in plasma lipoproteins or hepatic lipid content. Both LCMUFA isomers significantly decreased plasma CRP levels, improved Abca1-dependent cholesterol efflux capacity of apoB-depleted plasma, and enhanced Ppar transcriptional activities in HepG2 cells. LC-MS/MS proteomic analysis of lipoproteins (HDL, LDL and VLDL) revealed that both LCMUFA isomer diets resulted in similar potentially beneficial alterations in proteins involved in complement activation, blood coagulation, and lipid metabolism. Several lipoprotein proteome changes were significantly correlated with atherosclerotic plaque reduction. Conclusions: Dietary supplementation with the LCMUFA isomers C20:1 or C22:1 was equally effective in reducing atherosclerosis in LDLr −/− mice and this may partly occur through activation of the Ppar signaling pathways and favorable alterations in the proteome of lipoproteins. Highlights: Some fish oils are enriched in long-chain monounsaturated fatty acids (LCMUFA). LCMUFA isomers (C20:1, C22:1) fractions inhibited atherosclerosis in LDLR-KO mice. There were no major differences in plasma lipoproteins or hepatic lipid content. Proteomic analysis revealed lipoprotein composition changes by LCMUFA isomers. Several lipoprotein proteome changes significantly correlated with atherosclerotic reduction.